Brain metastases: pathobiology and emerging targeted therapies - Preusser, Matthias; Capper, David; Deimling, Andreas von; Winkler, Frank; Wick, Wolfgang (Acta neuropathologica, 2012)
Brain metastases (BM) are common in cancer patients and are associated with high morbidity and poor prognosis, even after intensive multimodal therapy including resection, radiotherapy (stereotactic radiosurgery or whole brain radiotherapy) and chemotherapy. However, advances in the understanding of the pathobiology of BM and the development of molecular targeted agents hold promise for improved prophylaxis and therapy of BM. Here we provide a comprehensive review of the current concepts on mechanisms of the brain-metastatic cascade involving hematogenous dissemination of tumor cells, attachment to microvessel endothelial cells, extravasation into the brain, interaction with the local microenvironment, angiogenesis and intraparenchymal proliferation. Transendothelial migration depends on adhesion molecules such as integrins, selectins and chemokines. Tumor cells invade the brain by degrading extracellular matrix components using heparanase and matrix metalloproteinases. Astrocytes and microglial cells exert not only anti-, but also pro-neoplastic effects on brain-invading tumor cells. Some tumor types (e.g. melanoma) show prominent cooption of preexisting vasculature, while other tumor types (e.g. lung cancer) tend to show early angiogenesis after brain invasion. In this article we also critically summarize the data on currently studied targeted therapeutics in BM especially in the context of recent preclinical data. The most promising agents for BM patients include anti-angiogenic drugs, inhibitors of v-RAF murine sarcoma viral oncogene homolog B1 (BRAF) for BRAF V600E mutated melanoma and inhibitors of epithelial growth factor receptor for non-small cell lung cancer. Molecular analysis of the BRAF V600E status of melanoma BM using DNA-based methods or immunohistochemistry may soon enter the routine neuropathological practice.